Management of Teaching to ready and writing through art therapy in children - Mariela González-López (Har Press Indonesia, 2021)
This method helps to identification learning problems in the process of reading and writing in children. Is a study qualitative, is based in a methodology action research, with objective the children teach reading and writing in Spanish with the collage technique and method literacy, through steps: a) The first moment, diagnosis; apply an exam about the ready and writing. b) Planning for development teaching of ready writing, thought collage technique, new tool of the therapy art, a didactic strategy is proposed to teach reading and writing, through the technique of collage. c) educative intervention for teaching literacy was done in a first-grade group with 27 students, through a series of steps, the figure is drawing whose name begins with the letter L-l, then they cut it out and they indicate to the students what it is, and the objective is that they learn the letters and what words can be written with that letter, also read the same, finally the child must paste cuts of a single-color favorite, using the common magazine. d) Analysis and conclusion, the effects of the collage technique of art therapy, children learn the letters and words through the process of literacy, using this method and time learning environments are presented to learn letters, syllables and words through of collage, a method of visual projection. Conclusion is that the method ready writing is new proposed for teach to ready and writing. Children learn their first words in the first month, in addition to reading and writing habits.